Pemanfaatan tepung kentang sebagai substitusi tepung terigu dalam pembuatan bolu marmer panggang: Use of potato flour as a substitute for wheat flour in making baked marble bolu - Pratiwi, Ardita Epi; Ngatirah; Sunardi (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Efforts to reduce the use of domestic wheat flour include the use of local food ingredients such as tubers. Potatoes can be used to make potato flour, a type of flour derived from potatoes that can be used as an alternative to adding wheat flour as a raw material in making sponge cake. This research aims to determine the effect of substituting potato starch for wheat flour on the physical, chemical, and hedonic characteristics of baked marble sponge cake. This research used a completely randomized design with 1 factor, namely the substitution of potato starch for wheat flour with 6 levels (A = 100%, B = 80%, C = 60%, D = 40%, E = 20%, and F = 0%) with 3 repetitions. The results showed that higher substituting potato starch significantly affects increasing of moisture and ash, reducing of fat, protein, and carbohydrate, increasing crude fiber, decreasing brightness value (L* value), and decreasing hardness, as well as affecting the texture, color and aroma preference tests. Based on the overall organoleptic test results, it showed that all treatments were liked by the panelists, however, based on texture, the best treatment was found in the sample with 80% potato starch substitution. The marble cake with the formulation of potato starch 80% and wheat flour 20% has good physical and chemical characteristics.